Woman in Journalism - Parkinson, Fannie (My University, 1896)
Introduction: Blessed is he who has found his work; let him seek no other blessedness,” says Carlyle. And may we not say as much for woman – Blessed is she who has formed her work? Perhaps no one but the woman who toils daily for her bread knows better how disagreeable it is, what a burden life is, when she must follow an occupation which is displeasing to her; when she cannot be allowed to choose that profession which alone has its peculiar charm for her and make it her life work. A popular writer on this topic has said, “How much happier that woman is, who can cheerfully take up the work she likes, than the one who toils daily at uncongenial unemployment.” The time has come.
Citation: Parkinson, Fannie. Woman in Journalism. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Women; Occupation; Employment; Theses; Manuscripts (documents)